Factors affecting pregnancy rates and calving difficulty in commercial beef heifers - Utter, S.D.; Houghton, P.L.; Corah, L.R.; Spire, M.F.; Higgins, James J.; Butine, M.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Data from yearling Angus and Angus crossbred beef heifers from a commercial ranch were used to identify factors affecting pregnancy rates (n=342) and calving difficulty (n=295). Production data analyzed included prebreeding weight, average daily gain during the breeding season, and postbreeding weight; evaluations of hip height, frame score, weight:height ratio, and reproductive tract score were made at approximately 1 yr of age. Pregnancy rates were affected significantly by weight:height ratio, prebreeding weight, and reproductive tract score. However, based on correlation coefficients, the magnitude of influence of these traits on first-service conception and overall pregnancy rates was low. Calving difficulty in the same heifers (n=295) was influenced significantly by calf birth weight, heifer yearling frame score, and average daily gain of the heifer during the breeding season. Heavier calf birth weight increased calving difficulty, whereas increases in frame score and average daily gain reduced calving difficulty.
Keywords: Beef; Heifer development; Pregnancy rate; Calving difficulty